腭裂患者错误构音的相关因素研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2014)
OBJECTIVE: To investigate the correlation between articulation, velopharyngeal function, and surgical age by comparing the changes in articulation after velopharyngeal closure is performed. This study is also conducted to investigate the influencing factors of omission change between pre- and post-operation. METHODS: A total of 48 patients, including 18 males and 30 females, mean age (13.3±5.8) years, with non-syndromic cleft lips and palates were selected from January 2011 to December 2011. Their speech data and articulation between pre- and post-operation were retrospectively analyzed using non-parametric tests. Correlation study was performed to analyze the influencing factors of the changes in articulation. P<0.05 was considered statistically significant. RESULTS: The difference in articulation after velopharyngeal closure occurred was significant (Z=−3.796, P=0.000). A negative correlation between the ratio of post-operative normal articulation and surgical age (R=−0.487, P=0.000) was observed. The change in omission was positively correlated with surgical age (R=0.589, P=0.000) and gender (R=0.404, P=0.047). By comparison, the change in omission was negatively correlated with follow-up time (R=−0.235, P=0.040). CONCLUSION: Articulation and intelligibility are significantly improved after velopharyngeal closure is performed. These parameters are negatively correlated with surgical age to some extent. In addition, the change in omission is positively correlated with surgical age and gender, whereas the change in omission is negatively correlated with follow-up time.